Flap Reconstruction of Sarcoma Defects in the Setting of Neoadjuvant and Adjuvant Radiation - Kadle, Rohini; Motosko, Catherine C.; Zakhem, George A.; Stranix, John T.; Rapp, Timothy; Saadeh, Pierre B. (Journal of Reconstructive Microsurgery, 2019)
Background Limb-sparing treatment of extremity soft tissue sarcomas requires wide resections and radiation therapy. The resulting complex composite defects necessitate reconstructions using either muscle or fasciocutaneous flaps, often in irradiated wound beds.Methods A retrospective chart review was performed of all limb-sparing soft tissue sarcoma resections requiring immediate flap reconstruction from 2012 through 2016.Results Forty-four patients with 51 flaps were identified: 25 fasciocutaneous and 26 muscle-based flaps. Mean defect size, radiation treatment, and follow-up length were similar between groups. More often, muscle-based flaps were performed in younger patients and in the lower extremity. Seventeen flaps were exposed to neoadjuvant radiation, 12 to adjuvant radiation, 5 to both, and 17 to no radiation therapy. Regardless of radiation treatment, complication rates were comparable, with 28% in fasciocutaneous and 31% in muscle-based groups (p < 0.775). Muscle-based flaps performed within 6 weeks of undergoing radiotherapy were less likely to result in complications than those performed after greater than 6 weeks (p < 0.048). At time of follow-up, Musculoskeletal Tumor Society scores for fasciocutaneous and muscle-based reconstructions, with or without radiation, showed no significant differences between groups (mean [SD]: 91% [8%] vs. 89% [13%]).Conclusion The similar complication rates and functional outcomes in this study support the safety and efficacy of both fasciocutaneous flaps and muscle-based flaps in reconstructing limb-sparing sarcoma resection defects, with or without radiotherapy.
Keywords: sarcoma; myocutaneous flap; lower extremity